False amoxicillin/clavulanic acid susceptibility in Bacteroides fragilis using gradient strip tests. (June 2021) - Rentenaar, Rob J.; Bovo-Heijmans, Bianca; Diggle, Joanna; Fluit, Ad C.; Wootton, Mandy
Abstract: Background: Repeatedly, too low MIC results were obtained in Bacteroides fragilis quality assessment strains, using gradient strip tests with a ratio of amoxicillin:clavulanic acid of 2:1. We aimed to find the most accurate available gradient strip tests for susceptibility testing of amoxicillin/clavulanic acid in B. fragilis in comparison with agar dilution with EUCAST methodology and breakpoints. Methods: Twenty-seven clinical B. fragilis isolates were investigated using gold standard EUCAST amoxicillin/clavulanic acid agar dilution (fixed clavulanic acid concentration at 2 mg/L, with increasing amoxicillin concentrations) as well as three commercial gradient strip tests: XL (ratio), AUG (ratio) or AMC (fixed concentration). Results: Using agar dilution (fixed concentration), 19 isolates were susceptible, 1 isolate was susceptible increased exposure (I) and 7 isolates were resistant. Categorical agreement of the gradient strip tests with agar dilution (fixed concentration) was 70% for XL (ratio), 71% for AUG (ratio) and 89% for AMC (fixed concentration). Very major error rates in comparison with agar dilution (fixed concentration) were 100%, 0%, and 0%, respectively. Conclusions: EUCAST breakpoint usage in amoxicillin/clavulanic acid susceptibility tests for B. fragilis should be accompanied by EUCAST methodology. When using alternative methods such as gradient strip tests, a higher degree of alignment with EUCAST methodology, such as using fixed clavulanic acid concentrations, improves precision. Highlights: Amoxicillin/clavulanic acid gradient strip test MIC results of Bacteroides fragilis using a fixed clavulanic acid concentration were acceptably concordant with EUCAST gold standard agar dilution MIC results. Gradient strip testing of Bacteroides fragilis using a ratio of amoxicillin to clavulanic acid resulted in smaller MIC ranges and low categorical agreement with EUCAST gold standard agar dilution. Some meropenem resistant division II B. fragilis isolates were amoxicillin/clavulanic acid susceptible.